THE NIDUS OF TUBERCULOUS INFECTION AS A RISK FACTOR OF MULTIPLE DRUG RESISTANT TUBERCULOSIS IN CHILDREN - V. A. Аksenovа; N. I. Klevno; S. M. Kаvtаrаshvili; A. V. Kаzаkov; A. D. Pаkhlаvonovа (Туберкулез и болезни лёгких)
The article presents a comprehensive description of tuberculous infection nidi, where children were exposed to this infection and developed multiple drug resistant tuberculosis. It was found out that the risk to develop MDR TB in children was also related to exposure to a TB case with undetected resistance to rifampicin, which was to be taken into account when prescribing the chemotherapy regimen.When prescribing preventive treatment to children exposed to MDR tuberculosis one should consider the potential risks and benefits.